FLOYD–WARSHALL ALGORITHM FOR SHORTEST ROUTE CALCULATION BETWEEN LATVIA’S CITIES - Gavars, Raivis; Netlis-Galejs, Einārs; Lazdiņš, Jānis Artūrs; Kangro, Ilmārs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2019)
The Floyd–Warshall algorithm is a good choice for computing paths between all pairs of vertices indense graphs, in which most or all pairs of vertices are connected by edges. For sparse graphs with non-negative edgeweights, a better choice is to use Dijkstra's algorithm from each possible starting vertex. Also, a very good thing is that thesolution is very accurate, when using a computer. In this paper, the authors tried to apply a solution using C++programming language to make possible many entries.